Magnetic and thermoelectric properties of melt-spun ribbons of Fe2XAl (X = Co, Ni) Heusler compounds - Saito, Tetsuji; Nishio-Hamane, Daisuke (Journal of applied physics, 2018)
The magnetic properties and thermoelectric properties of two Heusler compounds, the Fe2CoAl and Fe2NiAl phases, were investigated. The Fe2CoAl and Fe2NiAl compounds were ferromagnetic at room temperature and showed high saturation magnetization of 135 emu/g for the Fe2CoAl compound and 116 emu/g for the Fe2NiAl compound. Both compounds exhibited a high Curie temperature of around 1000 K. It was found that these compounds showed low electrical resistivity of less than 6.0 μΩm at room temperature. Thermoelectric measurements revealed that these compounds had negative Seebeck coefficients of −20 μV/K for the Fe2CoAl compound and −15 μV/K for the Fe2NiAl compound at room temperature.